Living the Good Life: The Effects of Job Variables on Nigerian Prison Staff Life Satisfaction. (December 2019) - Lambert, Eric G.; Elechi, O. Oko; Otu, Smart
Life satisfaction is an important concept for both workers and employing organizations. Past research on the spillover theory has found that higher life satisfaction results in lower absenteeism and turnover/turnover intent, higher job performance, and better mental and physical health. The current study examined how job variables (i.e., job stress, job involvement, and job satisfaction) were associated with life satisfaction among Nigerian prison staff in an attempt to determine whether the aforementioned workplace variables have similar or different effects across nations. Data for this study came from a survey of 120 responding staff at a prison located in the Ebonyi state in Southeast Nigeria. In a multivariate ordinary least squares regression analysis, job stress had significant negative effects on life satisfaction, and job involvement and job satisfaction had significant positive effects. The findings for job stress and job involvement are consistent with that found among U.S. correctional staff. The finding that job involvement had a significant positive effect differs from that reported for U.S. staff. The results suggest that prison administrators should attempt to lower job stress and increase job involvement and job satisfaction.